Numerical Modal Analysis of the Turbo-jet Engine Rotor Blades - Vavro, Jan; Vavro, Jan; Kianicova, Marta; Vavrova, Alena; Pecusova, Beata (Manufacturing Technology Journal, 2019)
The given paper is closely connected with the numerical modal analysis of eigenfrequencies and eigenshapes for turbine blades of the turbojet engine with the help of the mathematic modelling. The mathematic model was created in Pro-Engineer program and it was subsequently created to the ANSYS program in order to apply finite element method. Distribution of the stress in the turbine blades is presented in [Pa]. The presented results of the eigenshapes and distribution of the stress are obtained in the graphic form.
Keywords: modal analysis; eigenfrequencies; eigenshapes; stress; finite element method